Impact of HIV-1 viral load on genotypic characteristics among patients failing non-nucleoside reverse trancriptase inhibitor-based first-line regimens in Northern Thailand - Praparattanapan J. (2014)
Widespread use of antiretroviral drugs has significantly increased drug resistance. In the resource limited countries, delayed detection of drug resistance may lead to accumulation of drug resistance mutations. We investigated the genotypic drug resistance mutation patterns in HIV-infected patients with various levels of plasma HIV RNA levels. Fifty-nine HIV-infected patients with antiviral therapy failure were recruited. Genotypic assays of HIV-1 protease and reverse transcriptase genes were analyzed. There was a significant difference in CD4 cell counts and percentage of CD4 (p < 0.05) between groups of patients with high and low viral load, who failed first-line non nucleoside reverse transcriptase inhibitor-based regimens. In addition, patients with HIV-1 viral load ≥ 4 log10 have a significantly higher likelihood of being infected with HIV-1 containing 3 to 5 resistance-associated mutations than those with HIV-1 viral load < 4 log10. Thus, delayed detection of increased HIV-1 viral load and antiretroviral drug-resistance may lead to accumulation of drug-resistant mutations and decreased CD4 cell count and percentage.